2013
DOI: 10.1055/s-0033-1363326
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Various Surgical Delay Methods with Ischemic Preconditioning in the Rat TRAM Flap Model

Abstract: Both surgical delay and ischemic preconditioning (IP) have been shown to be effective in improving the survival of flaps. We used a variety of flap delay methods and IP to increase the surviving area of the transverse rectus abdominis musculocutaneous (TRAM) flap in rats, and the results are compared in between. A 6-× 3-cm-sized TRAM flap in 40 Wistar rats was allocated into five groups. Group 1: TRAM flap was elevated from nondominant pedicle, and the flap was sutured to the original bed. Group 2: Left superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Partial or total flap necrosis remains a major challenge in the field of pedicled flap surgery. The surgical delay has been demonstrated to be a reliable procedure to improve pedicled flap's survival area, but so far, the optimal delay period is still a controversial issue, which may be 5 days, 7 days, 14 days, 21 days, or 8–10 days in the literature . Thus, how to determine the optimal delay time continues to be unknown in the clinical practice, because various surgical delay animal models and delay procedures may significantly influence the delay period of reaching the maximal delay effect .…”
mentioning
confidence: 99%
“…Partial or total flap necrosis remains a major challenge in the field of pedicled flap surgery. The surgical delay has been demonstrated to be a reliable procedure to improve pedicled flap's survival area, but so far, the optimal delay period is still a controversial issue, which may be 5 days, 7 days, 14 days, 21 days, or 8–10 days in the literature . Thus, how to determine the optimal delay time continues to be unknown in the clinical practice, because various surgical delay animal models and delay procedures may significantly influence the delay period of reaching the maximal delay effect .…”
mentioning
confidence: 99%
“…11 Various successful results have been published using the cross-leg method. [19][20][21][22][23][24][25][26][27][28][29][30] Yu et al published an 85-case series using the cross-bridge method and reported a success rate of 95.29%. 20 The advantages of reconstruction with cross-leg free flaps include the possibility of preparation with the required tissue components such as bone and muscle of the requisite sizes and allowing the anastomosis line to be completely outside the trauma zone.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the ischemic preconditioning for the early division of a flap's vascular pedicle can be applied extensively with minimal discomfort. 26,32 This is also an option for surgeons to consider. In theory, all types of free flaps can be applied in cross-leg free flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion injury by abrupt restoration of circulation after the prolonged ischemia has long been a big problem in plastic and reconstructive surgery. 9 Multiple therapeutic strategies have been proposed in an attempt to attenuate I/R injury, 22,34,35 among which the post-con procedure is the one that has been investigated as the most promising protocol. post-con was first described in 1996, which involves intermittent cycle reperfusion after ischemic insult.…”
Section: Discussionmentioning
confidence: 99%